PENJATUHAN PIDANA RINGAN TERHADAP TINDAK PIDANA KESUSILAAN YANG DILAKUKAN OLEH ANGGOTA TNI (STUDI PUTUSAN PENGADILAN MILITER III-17 MANADO NOMOR 56-K/PM.III-17/AD/IX/2024) - Bambang Aribowo; Indah Sari (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
Criminal offense of decency are a type of offense closely related to violations of moral and ethical norms that are highly upheld in society. Perpetrators of crimes against morality are not only from civilian circles but can also come from the military, namely the Indonesian National Armed Forces (TNI). This research was conducted using a normative juridical research method, which involves studying literature or secondary data sources. The author used a case approach. The regulation of crimes against morality in the Indonesian Penal Code (KUHP) is stipulated in Book Two, Chapter XIV, and Book Three, Chapter VI. In the latest version of the KUHP, namely Law Number 1 of 2023, such regulation is found in Article 406. A member of the military or a TNI personnel involved in a crime against morality is still subject to the provisions of general criminal law. The imposition of a light sentence on the defendant in the Manado Military Court III decision number 56-K/PM.III-17/AD/IX/2024—ten months of imprisonment, reduced by time already served—does not correspond to the aggravating factors, such as the defendant’s actions harming the victim, disturbing the public, and violating societal moral norms, especially considering that the defendant is a member of the TNI. There is a need to evaluate and revise the military legal system, which still allows for lenient sanctions in cases of crimes against morality. It is hoped that the Military Court, in handing down decisions related to crimes against morality committed by TNI members, can more proportionally consider the values of justice for the victims and the social impacts caused.